Surmonter les limites naturelles : l’exemple des populations indigènes de la Basilicate - Maria Pina Garaguso (Frontière·s)
Basilicata is a region of southern Italy that appears as a land of strong orographic contrasts. It is characterized by a mountainous area carved by five rivers, crossing from west to east. As a rule, settlement patterns follow the region’s topographic characteristics. The rivers are thought of as natural limits, but are also considered privileged means of communication that allowed the indigenous populations of the more internal areas to maintain many relations with the poleis of the Ionian coast. Two Greek cities were founded on the coast, at the mouths of the main rivers: Siris, between the mouths of Agri and Sinni, and Metaponto between those of Bradano and Basento. From the end of the 7th century BCE onwards, it is possible to trace back the preferred routes along which Greek objects travelled. After crossing the borders of the chora, these artefacts integrated the indigenous funerary repertoire.